1998
DOI: 10.1002/ana.410430109
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 14‐3‐3 protein in the cerebrospinal fluid supports the diagnosis of Creutzfeldt‐Jakob disease

Abstract: The analysis of 14-3-3 protein in cerebrospinal fluid (CSF) was shown to be highly sensitive and specific for the diagnosis of Creutzfeldt-Jakob disease (CJD). However, the predictive value of this test in the clinical diagnosis of, and its relation to, sporadic, genetic, and iatrogenic CJD cases have yet to be established. CSF samples of suspect CJD cases seen in the prospective German surveillance study were tested for the presence of 14-3-3 protein by using a modified western blot (WB) technique. WB detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
242
3
18

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(270 citation statements)
references
References 35 publications
7
242
3
18
Order By: Relevance
“…If similar changes are detectable in more easily accessible biospecimens, including CSF and plasma, 14‐3‐3 phosphorylation has the potential as a biomarker for neurodegeneration. Measurement of 14‐3‐3s in CSF has been used clinically as a diagnostic biomarker for Creutzfeldt‐Jakob Disease (CJD), although recent studies have demonstrated that the specificity for CJD is lower than initially thought 48, 49, 50, 51. However, this body of research has demonstrated that 14‐3‐3 measurements in CSF are reliable and stable in patients, and can help with diagnosis in the right clinical context 48, 49.…”
Section: Discussionmentioning
confidence: 99%
“…If similar changes are detectable in more easily accessible biospecimens, including CSF and plasma, 14‐3‐3 phosphorylation has the potential as a biomarker for neurodegeneration. Measurement of 14‐3‐3s in CSF has been used clinically as a diagnostic biomarker for Creutzfeldt‐Jakob Disease (CJD), although recent studies have demonstrated that the specificity for CJD is lower than initially thought 48, 49, 50, 51. However, this body of research has demonstrated that 14‐3‐3 measurements in CSF are reliable and stable in patients, and can help with diagnosis in the right clinical context 48, 49.…”
Section: Discussionmentioning
confidence: 99%
“…CSF proteins evaluation: 14-3-3, Ab42, t-tau, p-tau and S-100b CSF samples, collected in sterile polypropylene tubes, were centrifuged at 2,500 rpm for 5 min, aliquoted and stored at -80°C until analysis. Immunodetection of protein 14-3-3 in CSF was done as described previously [42], with minor modifications. Briefly, CSF proteins were separated by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and detection was carried out by incubation with mouse anti-14-3-3 beta monoclonal antibody (sc-1657, Santa Cruz Biotechnology, USA) followed by horseradish peroxidaseconjugated anti-mouse immunoglobulin (DakoCytomation, Denmark).…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Immunodetection of protein 14-3-3 in CSF was originally demonstrated to have a high sensitivity and specificity for sCJD [19,42] and has, therefore, been included by the World Health Organization (WHO) in the diagnostic criteria for probable disease [41]. However, this view has been challenged by findings of poor specificity [6,7] and low sensitivity in autopsy-proven sCJD cases [11].…”
Section: Introductionmentioning
confidence: 99%
“…The 14-3-3 protein in the CSF has been reported to have a sensitivity between 85% and 96% and a specificity between 79% and 96%. As it may be present in other conditions such as viral encephalitis, metabolic encephalopathy and cerebral hemorrhages, the test is not appropriate as a general screening test for CJD, but is useful for diagnosis of truly suspect cases (14)(15)(16). In contrast to qualitative 14-3-3 test, ELISA immunoassay for the quantitative detection of tau protein in CSF has shown superior accuracy with less ambiguous results (17).…”
Section: Discussionmentioning
confidence: 99%